The effect of swimming learning aids on swimming learning outcomes for children aged 6-8 years - Muhammad Iqbal; Bayu Budi Prakoso; Setiyo Hartoto; Fifukha Dwi Khory (Universitas Sriwijaya, 2025)
Research Problems: Swimming learning in Indonesia, especially in schools, still faces many obstacles that must be considered. The problem that often occurs is the limited availability of adequate facilities. Many educators or trainers complain about the existing facilities, especially in rural areas. Research Objectives: This research aims to utilize assistive devices for swimming learning outcomes in children aged 6-8 years. Method: This research uses an experimental research method with a One Group Pretest-Posttest Design research design. The population used was all 50 children who took part in Club Aquaspint. Sampling used a purposive sampling technique and obtained a sample of 17 children. The research instrument was carried out by observation. Data analysis uses descriptive statistics which includes descriptive data analysis, normality test, homogeneity test, and hypothesis test. Results: The results of the pretest descriptive statistical data analysis obtained a mean value of 8.29, while the post-test obtained a mean value of 11.24. The results of the pretest and post-test hypothesis tests on Equal variances assumed obtained a tcount value of 7.773 > ttable value of 2.131 or a significance value (2-tailed) of 0.000 < 0.05, so Ha was accepted, and Ho was rejected. Conclusion: It can be concluded that there is an influence of swimming learning aids on the swimming learning outcomes of children aged 6-8 years. The limitation that researchers found was that this study only involved 17 children aged 6-8 years, so the results cannot be applied to children outside that age range.